Special section (MAT435/MAT235): common errors in mathematics / Hasfazilah Ahmat and Noor 'Aina Abdul Razak - Ahmat, Hasfazilah; Abdul Razak, Noor 'Aina (Unit Penerbitan JSKM, 2020)
This special section covers the errors that the students often make in doing Algebra, and not just errors typically made in an algebra class. These mistakes, in fact, make by students at all level of studies. The earlier examples are the errors commonly done in a math class not limited to the calculus class.